Faktor Tampilan dan Penyesuaian Aplikasi pada Kualitas Layanan dalam Menganalisis Loyalitas Pengguna Transportasi Daring - Michael Christian (JIEMS (Journal of Industrial Engineering and Management Systems), 2020)
The shift in the pattern of using land transportation modes from conventional to online application-based has helped shape the lifestyle pattern of using different land transportation modes for the community. However, the other side of the presence of this application-based online land transportation mode is to maintain customer needs and expectations through aspects of service quality in applications provided by application-based online transportation service providers. It is not an easy thing to do and maintain. Applications should have quality because applications are the main capital in using online transportation modes. In addition, the information listed on the online transportation mode application is an important factor in providing the suitability of the information in the application. This study aims to analyze the effect of application display factors and feature adjustments in the application on user loyalty of application-based online transportation modes. By using SMART PLS 3.0, the results of this study explain that the attitudes of users of application-based online transportation modes are influenced by the application display factors and the adjustment of features in the application. Furthermore, loyalty is influenced by the attitude of users of application-based online transportation modes. Other recent features as part of service quality can be another factor that can be used to analyze user loyalty for application-based online transportation modes. This is useful for enriching understanding in determining the loyalty of users of application-based online transportation modes.